Can topical calcipotriol be a treatment alternative in actinic keratoses? A preliminary report - (:unkn) unknown (My University, 2009)
BACKGROUND: Recent research demonstrated that vitamin D, apart from calcium-related actions, has antiproliferative, prodifferentia-tive and immunomodulatory activities. OBJECTIVE: To determine whether actinic keratoses may benefit from the antiproliferative and prodifferentiative effects of topical vitamin D. MATERIALS AND METHODS: The study was an investigator-blinded, half-side comparison trial. Patients applied calcipotriol cream to one side and Ultrabase cream as placebo to the other side of the scalp and/or face for 12 weeks. The total number of actinic keratoses (AKs), diameters and total scores of the target lesions were determined at each visit. RESULTS: Nine patients were included, eight of whom completed the treatment. There was a statistically significant difference between the total number of AKs at baseline and at week 12 on calcipotriol applied side whereas no difference was detected on placebo applied side (p = 0.028 vs p = 1.00). The mean total score of the target lesions reduced significantly at week 12 on calcipotriol side; however, no significant reduction was found on placebo side (p = 0.017 vs p = 0.056). Although side effects were more common on calcipotriol side, the difference was not statistically significant. CONCLUSION: Topical calcipotriol may show promise in the treatment of actinic keratoses. More studies are needed to confirm its efficacy.
Keywords: Female; Humans; Middle Aged; Aged; Aged, 80 and over; Male; Administration, Topical; Drug Administration Schedule; Single-Blind Method; Dermatologic Agents; Calcitriol; Keratosis, Actinic